Dimensions of Coping in Individuals Facing Long-Term Unemployment - Rahman, Farhana; Benali, Youssef; Popescu, Andreea (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore and categorize the dimensions of coping strategies employed by individuals facing long-term unemployment in Morocco. Methods and Materials: A qualitative research design was adopted, utilizing a phenomenological approach to capture the lived experiences of participants. Twenty-seven individuals (14 males, 13 females), aged between 23 and 54 years, who had been unemployed for a minimum of 18 consecutive months, were purposively sampled from both urban and rural regions of Morocco. Data collection was conducted through semi-structured, in-depth interviews, either face-to-face or via secure online platforms, depending on participants’ preferences. All interviews were transcribed verbatim and analyzed using thematic analysis in NVivo 14 software, following an inductive coding process to identify categories, subcategories, and concepts. Findings: Analysis revealed four main dimensions of coping: emotional coping strategies, social and relational coping, cognitive and problem-focused coping, and behavioral and lifestyle adaptations. Emotional coping encompassed subthemes such as emotional regulation, positive reframing, suppression of negative emotions, acceptance, and hope maintenance. Social and relational coping included family support, peer networks, community engagement, reduced social interaction, online social support, and mentorship seeking. Cognitive and problem-focused coping involved skill development, goal setting, job search strategies, financial planning, information seeking, self-monitoring, and creative problem-solving. Behavioral and lifestyle adaptations comprised routine maintenance, health-oriented activities, leisure and hobbies, religious and spiritual practices, relocation or migration planning, temporary or gig work, and minimalist living. Conclusion: Effective support interventions should integrate skill-building, emotional well-being enhancement, and community-based resources to address both the immediate and long-term needs of unemployed individuals.